(untitled) (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2016)
This article – with the help of the population census from 2001–2011 – seeks to document a thorough and comparative examination of the employment case of people with mobility disability in Transdanubia. After introducing the region’s economic activity (with the help of the results of a future dissertation which examines the employment characteristics of 20 Transdanubian companies from the aspects of both the employer and the employee) the study reveals the labour market possibilities of the people with mobility disability in the region.